2018
DOI: 10.1371/journal.pone.0207388
|View full text |Cite
|
Sign up to set email alerts
|

Effect of anaesthetic technique on neonatal morbidity in emergency caesarean section for foetal distress

Abstract: BackgroundWhile foetal distress is typically associated with ischaemic injury, few studies have assessed neonatal morbidity for emergency caesarean section. Moreover, the decision of the anaesthetic technique may be of paramount importance in emergency caesareans, because of the limited time and increased risk. We aimed to evaluate the effect of the anaesthetic technique on neonatal morbidity in emergency caesarean indicated for foetal distress.MethodsThis was a single-centre, prospective observational study, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
1
6

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 24 publications
1
20
1
6
Order By: Relevance
“…Our ndings are consistent with those of several other studies in Africa, Europe and the USA, where GA was seen to be associated with lower APGAR scores, following anaesthesia for AFD. However, unlike our study, their results showed that lower APGAR scores following GA was signi cant even at the 5 th minute following delivery (15), (16), (17). GA is shown in our study to be associated with signi cantly higher chances of neonatal resuscitation when compared to SA.…”
Section: Discussioncontrasting
confidence: 97%
“…Our ndings are consistent with those of several other studies in Africa, Europe and the USA, where GA was seen to be associated with lower APGAR scores, following anaesthesia for AFD. However, unlike our study, their results showed that lower APGAR scores following GA was signi cant even at the 5 th minute following delivery (15), (16), (17). GA is shown in our study to be associated with signi cantly higher chances of neonatal resuscitation when compared to SA.…”
Section: Discussioncontrasting
confidence: 97%
“…In contrast, it has been reported that the “traditional” low APS defined as < 7 remains relevant for the prediction of neonatal adverse outcomes 10 , 11 . Some significant studies showed that APS at 5 min was a prognostic factor of neonatal adverse outcomes 2 , 10 , 12 and indeed chose APS at 5 min as a measure to evaluate neonatal outcomes 5 , 13 . In a joint statement issued by the Japan Society of Obstetrics and Gynecology and the Japan Association of Obstetricians and Gynecologists, neonatal asphyxia was defined as a case with 5-min APS of < 7.…”
Section: Resultsmentioning
confidence: 99%
“…In an analysis of the data for 113,300 preterm infants from the Swedish Medical Birth Register, APS at 5 and 10 min provided prognostic information about neonatal survival 12 . In a prospective study investigating the effect of anesthetic technique (GA vs. SA) on neonatal morbidity in emergency CS for fetal distress, the neonatal morbidity was defined as a 5-min APS < 7, need for mechanical ventilation, admittance to a neonatal intensive care unit, or respiratory insufficiency symptoms 13 .…”
Section: Methodsmentioning
confidence: 99%
“…This may be because of hypotension following RA that can decrease uteroplacental perfusion and produce fetal acidosis [6,15,16], although in some studies, GA was associated with lower pH values [17,18]. Edipoglu et al [19] found that umbilical blood pH with GA is associated with lower pH values (7.20 for GA versus 7.29 for RA), although this difference was not statistically significant (p > 0.05). In our study, we also did not find a statistically significant difference in umbilical cord pH, and base excess (all p>0.05) [GA -pH:7.36 (6.72-7.53) versus RA pH: 7.35 (7.04-7.56) ].…”
Section: Discussionmentioning
confidence: 99%